THE USE OF PEER FEEDBACK TO ENHANCE STUDENTS ABILITY TO WRITE DESCRIPTIVE TEXT - Mahdiyyah, Khadijah; Herawati, Atti; Vonti, Lungguh Halira (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
Writing is one of productive skills that is different from other skills. In writing, students need more time to express their idea in a written form. Besides, teacher also needs time to give feedback to motivate the students in revising their work. To make the activity of giving feedback more effective and efficient, this research was conducted. It is aimed to find out whether peer feedback has positive effect or not in enhancing students ability to write descriptive text. This research involved the third semester students of English Language Education Study Program, Pakuan University. The sample was 21 students from semester 3A. They were chosen by using random sampling technique. The researcher used quantitaive approach and applied pre-experimental method. She chose one group pre-test post-test design. The instrument of this research was writing test to measure students ability to write descriptive text. In addition, the data were analyzed by using t-test formula. From the calculation, she finds the result of t-test value is 9.41 meanwhile the t-table value is 2.09 from the significant level 0.05 with the degree of freedom (df) is 20. It means that the t-test value is higher than t-table value (9.41 more than 2.09). The calculation indicates that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Thus, peer feedback affects students ability to write descriptive text.